ANALISIS PERKEMBANGAN KAWASAN PERMUKIMAN SEKITAR DANAU TONDANO KABUPATEN MINAHASA - Brigita T. Makarawung; Rieneke L. E. Sela; Leidy M. Rompas (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
In the Minahasa Regency RTRW the area around Lake Tondano is designated as a protected area, in fact the existing protected area has been used as a place to live for the existing community to fulfill human interests. Lake Tondano. The community's need for land as a place to build houses is decreasing due to population growth. People's houses are no longer around the lake, but have penetrated to the waters. Therefore, a research was carried out with the aim of identifying the development of residential areas around Lake Tondano and calculating the area of development of residential areas around Lake Tondano. The research method used in this research is spatial time series analysis to see the development of residential areas and quantitative descriptive analysis . The results showed that the area around Lake Tondano experienced settlement development from 2003 to 2019, the area of settlement development from 2003 to 2011 grew by 87 ha, while the development of settlements in 2011 to 2019 increased by 132.58 ha. So that the distribution area of settlements from 2003-2019 is 413.76 ha to 633.81 ha.